Moisture absorption and dynamic flavor changes in hydrolysed and freeze-dried pine nut (Pinus koraiensis) by-products during storage. (January 2018) - Lin, Songyi; Yang, Ruiwen; Cheng, Sheng; Wang, Ke; Qin, Lei
Abstract: In the present study, two different fractions of pine nut ( Pinus koraiensis ) protein hydrolysate powder (PNPHP1–3 kDa and PNPHP3–10 kDa ) were prepared and stored for fifteen days at 25 °C and 50% relative humidity. Changes in moisture absorption, secondary structure and flavor compounds were measured at various time intervals over fifteen days. Results showed that the PNPHP3–10 kDa had higher moisture absorption capacity from day 6 to day 15 and that the secondary structure of two PNPHP fractions was changed. Major nine and eight flavor compounds were identified from PNPHP1–3 kDa and PNPHP3–10 kDa, respectively. PNPHP1–3 kDa mainly generated aldehydes and PNPHP3–10 kDa generated pyrazines. Finally, the formation of pyrazines was conjectured. The data suggests that Maillard reaction, microbial fermentation and lipid oxidation occurred during storage. The reactions appeared to be strongest by the sixth day. Graphical abstract: Highlights: Traced the difference of moisture absorption in PNPHP fractions Differences in 15 days' storage were determined by FT-MIR and SPME-GC–MS. PNPHP1–3 kDa mainly generated aldehydes and PNPHP3–10 kDa generated pyrazines PNPHP3–10 kDa had higher absorption capacity and intensity of flavor compounds. The formation of pyrazines was generated because of Maillard reaction.